Pengaruh audit tenure, workload auditor, reputasi auditor, dan fee audit terhadap kualitas audit dengan risiko perusahaan sebagai variabel moderasi - Nurfadhilah Zahra; Harry Budiantoro (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
The growing need for dependable financial statements, driven by fierce economic rivalry and the rising number of public firms, necessitates auditors to provide superior audit quality. Nonetheless, prior research on the determinants of audit quality continues to provide incongruous findings. This research seeks to examine the impact of audit tenure, auditor workload, auditor reputation, and audit fee on audit quality, with company risk serving as a moderating variable. This study employs a quantitative methodology. This study's population comprises 15 firms listed on the SRI-KEHATI index from 2019 to 2023. Data analysis was performed using multiple linear regression and Moderated Regression Analysis (MRA) with the aid of SPSS software. The t-test findings demonstrate that audit fees positively influence audit quality, but Audit tenure, auditor Workload, and auditor reputation do not impact audit quality. The moderation test findings indicate that business risk may moderate the impact of auditor Workload on audit quality, but it cannot moderate the effects of Audit tenure, auditor reputation, and audit fee on audit quality. The results suggest that increased audit fees may enhance audit quality, but business risk might amplify the impact of auditor Workload on audit quality.